First record of Polyneura bonnemaisonii (Delesseriaceae, Rhodophyta) from the Atlantic Ocean of Africa. (22nd September 2015) - Hassoun, Mustapha; Moussa, Hanaa; Zbakh, Hanaa; Riadi, Hassane; Kazzaz, Mohamed; Salhi, Ghizlane
Abstract : A red algal species, Polyneura bonnemaisonii (Delesseriaceae, Rhodophyta), is described for the first time in the Atlantic Ocean of Morocco. This is also the first reference of the occurrence of this species in Africa. This species was collected in the lower intertidal to subtidal zones, from Hyayda (north-west of Morocco). The Moroccan specimen is studied in detail and compared with other closely related species. Habitat, geographic distribution, description and illustration of the macroscopic and microscopic characters are presented and discussed in this work.